(untitled) (Conferencea, 2023)
I. V. Palashevskaya stated that concepts are the basic units of culture in the mental world of a person, including information about the actual or possible state of things in the world (that is, what a person thinks, knows, guesses, imagines about the objects of reality). Concepts unite the entire paradigm of the world, from the perception of the world and everyday life as elements of the conceptual image of the world to the scientific interpretation reflected in the concepts. Therefore, the concept is a semantic formation that includes subjective meanings and generally accepted traditional meanings, that is, all potential semantic content of a cognitive object or event.